Indications of Creeping Acquisition through Rights Issues in Indonesian Non Financial Companies during 2018-2021 - Zafirah Rizka; Nur Dhani Hendranastiti (Universitas Negeri Semarang, 2023)
Creeping acquisition (CA) which happens all around the world could harm the market. This research discusses CA activities through rights issue (RI) transactions in the Indonesian capital market for publicly listed non-financial institution companies during 2018 – 2021. The method used in this study is a quantitative method with a cross sectional design to. The regressions used are linear and logistics, using 180 purposive samples of entities. The results of the study show that rights issuing companies experienced greater changes in investor share ownership, so do the business group rights issuing companies. Rights issuing companies experienced relatively large changes in investor ownership, namely >3% in the year prior to the issuance of the rights issue, thus increasing the company's intention to issue rights. But when viewed from the investors activities such as selling or capital expanding who loss >3%, it does not increase the company's intention to issue rights in the following year. RI with non-specific objectives does not have a stronger impact on changes in investor's share ownership of >5% in the company.